Design and testing of a microelectrode array with spatial resolution for detection of cancerous cells in mixed cultures - Giana, Fabián Eduardo (2019)
We present the design, construction and testing of a microelectrode array with spatial resolution which can be used for the detection of cancerous cells in a mixed cell culture by means of the impedance spectroscopy technique. Two different microelectrode diameters, namely 57 m and 211 m, were tested. A layer of an AuCu alloy was deposited between the glass substrate and the exterior Au layer, enhancing the adhesion of the microelectrodes to the substrate and at the same time showing lower impedance than the commonly used material Au. Characteristic features were extracted from the impedance measurements at different phases (growth, confluence, wound and healing) and used to feed a Linear Discriminant Analysis algorithm in order to discriminate between normal and cancerous cells. Relevant statistical tests were applied in the discrimination model for each phase. Finally, it was determined that the larger microelectrodes have a superior discriminant capacity: no incorrect classifications were obtained with microelectrodes measuring 211 m in diameter, while 23.5% false positives and 5.6% false negatives were obtained with 57 m microelectrodes.